VALIDATION OF THE REGISTRATION FORM OF THE NURSING CARE PROCESS IN THE PEDIATRIC SERVICES OF THE HUANCAVELICA REGIONAL HOSPITAL - PERU - Chenet Zuta, Manuel Enrique (2019)
The objective of the study was to validate the useof the nursing care process registration format usingthe NANDA-I NOC Taxonomy, NIC in the nursingservice of the Regional Hospital of Huancavelica.The design was prospective of applied, descriptiveand explanatory type. The sample consisted of 11nurses from the pediatric emergency service, whoparticipated as an experimental group, and 10 nursesfrom the pediatric service, who participated as acontrol group. In the results it was observed that, inthe post test, 100% of the nurses of the experimentalgroup apply the standardized model of the TaxonomyNANDA, NOC, NIC. In the control group, 80.0% doesnot apply the standardized model of the TaxonomyNANDA, NOC, NIC. The conclusion was that ofthe 100% of nurses in the experimental group, only27.3% know the management of the registrationformat with the NANDA NOC Taxonomy, NIC, whileof the 100% of nurses in the control group only 20%know the management of the Registration format ofthe nursing care process with the Taxonomy NANDA,NOC, NIC.